2020
DOI: 10.3390/rs12050761
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Relationship Between Microseisms and Spatial Distribution of Sea Wave Height by Statistical and Machine Learning Approaches

Abstract: Global warming is making extreme wave events more intense and frequent. Hence, the importance of monitoring the sea state for marine risk assessment and mitigation is increasing day-by-day. In this work, we exploit the ubiquitous seismic noise generated by energy transfer from the ocean to the solid earth (called microseisms) to infer the sea wave height data provided by hindcast maps. To this aim, we use a combined approach based on statistical analysis and machine learning. In particular, a random forest mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…At the same time, different studies showed the effectiveness of seismic noise monitoring as a tool to quantify human activity and its changes over time (Dias et al, 2020;Hong et al, 2020;Lindsey et al, 2020;Poli et al, 2020). Indeed, the Earth is continuously vibrating due to a wide spectrum of elastic energy sources including tectonic forces (Stein and Wysession, 2003), volcanic processes (Chouet and Matoza, 2013), the ocean (Cannata et al, 2020b) and human (Diaz et al, 2017) activity. As for the last point, it typically generates a high-frequency continuous signal (>1 Hz), called anthropogenic or cultural seismic noise, associated with phenomena such as traffic, construction, industrial operations and mining (Diaz et al, 2017;Hong et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, different studies showed the effectiveness of seismic noise monitoring as a tool to quantify human activity and its changes over time (Dias et al, 2020;Hong et al, 2020;Lindsey et al, 2020;Poli et al, 2020). Indeed, the Earth is continuously vibrating due to a wide spectrum of elastic energy sources including tectonic forces (Stein and Wysession, 2003), volcanic processes (Chouet and Matoza, 2013), the ocean (Cannata et al, 2020b) and human (Diaz et al, 2017) activity. As for the last point, it typically generates a high-frequency continuous signal (>1 Hz), called anthropogenic or cultural seismic noise, associated with phenomena such as traffic, construction, industrial operations and mining (Diaz et al, 2017;Hong et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have applied a more physics-based approach to quantitatively link microseism and sea wave height [ 170 , 171 , 193 , 194 ]. Cannata et al [ 180 ] analyzed the microseism recorded by six seismic stations located close to the Eastern Sicilian coastline, and proposed a machine learning-based approach to calculate a regression model for reconstructing the temporal and spatial variation in sea wave height using the microseism recorded at multiple seismic stations in different frequency bands.…”
Section: Measurement Based On Microseism Observationsmentioning
confidence: 99%
“…In addition, microseism is recorded continuously with a sampling frequency from tens to hundreds of Hz and is acquired at a very high temporal resolution. The spatial resolution depends on the number of stations installed close to the coastline [ 180 ]. Furthermore, in most areas, it is not necessary to install a seismic network specifically to record the microseism and then for sea wave height monitoring, but it is possible to use the seismic stations installed to monitor seismic and volcanic activities.…”
Section: Measurement Based On Microseism Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Serafino et al (2021), simultaneous measurements of a micro-seismic based system (called OS−IS) and those of a radar system were compared for the first time. In Cannata et al (2020), a machine learning method (specifically, a random forest) was proposed to reconstruct the spatial distribution of sea wave height, as provided by hindcast maps of sea wave models, by using micro-seismic data from multiple seismic stations. In Moschella et al (2020), a network of broadband seismic stations was used to investigate the microseismic signals from Ionian and Tyrrhenian Sea and, importantly, it was demonstrated that the signal detected by seismic stations closer to the sea contain more information concerning the sea state than the others.…”
Section: Introductionmentioning
confidence: 99%